Tela’ah Hadits Memelihara Anjing dengan Pendekatan Tasawuf: (Kajian Ma’anil Hadis) - Restu amandani; Muhajirin; Sulaiman Mohammad Nur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Caring for animals is often a friend and necessity for humans, whether they are herbivores, carnivores or even omnivores. Dogs are one of the animals that are often kept by some humans. The rise of dog lovers in Indonesia, including some Muslims, raises a big question, whether this is religiously permissible or the opposite. While in the hadith as a source of Islamic law, this is prohibited, but in essence it provides benefits for certain activities and actions. The researchers' anxiety arose, is the dog in the hadith only meant as a care animal or does it actually have an implied (philosophical) meaning? To reveal this meaning, the researcher used a qualitative method from a Sufism perspective, what exactly is the implied meaning of the word dog. In the end, it was concluded that in Sufism the meaning of dogs in the hadith are despicable qualities that have potential in the human heart. This research implies that the word dog in the hadith contains hidden meanings and can be used as an I'tibar in life.